Principal molecular markers (Research, Society and Development, 2021)
Molecular markers are molecular phenotypes originating from any expressed or unexpressed segments of DNA that come from genetic inheritance and lend themselves to the differentiation of one or more individuals. It can be classified into two groups: the first, markers are obtained by hybridization and the second, markers are obtained by DNA amplification. Among those identified by hybridization are the main RFLP markers and minisatellite markers, while for the markers by amplification are the most used RAPD, SCAR, STS, AFLP and SSR or microsatellites. In view of this, the present study aimed to develop a literature review on the main molecular markers and their respective information. The work seeks to synthesize the knowledge about the main molecular markers, because from them, it is possible to make the detection and analysis of genetic polymorphisms that are of interest in several areas, because they can help understand the molecular basis of various biological aspects. In view of this, the study by means of literature review becomes useful, showing how important molecular markers have been, because they can detect and analyze the genetic polymorphisms present in several species. And from the survey of journals in the last five years, it shows that RFLPs markers have the largest number of studies done, followed by SSRs and AFLPs markers. New studies can be made taking into consideration more years for the survey, obtaining more concrete and detailed results.